Authentic Assessment Innovation In Arabic Vocabulary Test: A Case Study Of TKIT Yasmin Muadz Bin Jabal - Sulistyaningsih, Sulistyaningsih; Baroroh, R Umi (UIN Sultan Maulana Hasanudin Banten, 2025)
This study aims to evaluate and develop assessment methods in Arabic language learning, especially in the aspect of mufrodat, at TKIT Muadz Bin Jabbal. The results showed that the assessment has not covered all aspects of learning thoroughly. Therefore, an authentic assessment approach is needed that assesses the process to learning outcomes. This authentic assessment is designed through fun, contextual, and interactive activities, such as matching words with pictures, following verbal instructions, or creating simple works. The approach helps children understand mufrodat more effectively by linking learning to everyday experiences. This innovation is expected to create a more meaningful and enjoyable learning process for early childhood.